Postkarte aus der Serie Dein Freund Das Tier. Herausgegeben zur Bundestagswahl am 2.12. 1990 - Schlegel, Marlies,
Postkarte aus der Serie Dein Freund Das Tier. Herausgegeben zur Bundestagswahl am 2.12. 1990.